Why conflicts emerge understanding intergroup conflict in Boracay Airport expansion using positioning theory. - Daguno, Richelle A.; Villar, Jolinnah T. (2016.)
Previous studies on intergroup conflict used social psychological theories that have a similar eye for mentalism, thus, limiting their ability to capture the dynamic and complex nature of intergroup conflict. Therefore, Positioning Theory, which addresses these limitations of such social psychological theories, is used in analyzing the Boracay Airport expansion intergroup conflict. In-depth interview was used as a data-collecting tool in this study. On data analysis, positioning analysis was utilized, thus, three categories: Economic Development, Social Justice, and Legal Conformity were constructed. Moreover, each category includes two contesting major storylines derived from narratives from the interviewees. The study found that the contention on perceived source of and solution to conflict is the root cause of the Boracay Airport expansion intergroup conflict.
Research Paper (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Boracay Airport -- Expansion